Density measurements of laser interaction with ordered structured 'snow' targets. (1st May 2014) - Schleifer, E.; Botton, M.; Nahum, E.; Eisenman, S.; Zigler, A.; Henis, Z.
Abstract: This paper presents a new method to control the position of a micro-column snow target. This target enables the measurement of the mean electron density of the pre-plasma created by a pre-pulse with different time delays. This research will allow a better understanding of the generation of fast protons from the interaction between a structured pre-plasma and a high intensity laser.